Emergency service system for urban population: problems and directions of perfection - N. G. Zenkin (Бюллетень сибирской медицины, 2003)
Perfection of emergency service is one of the most important task of the structure reforming of public health protection. Currently, the main tasks are: development and application of economic mechanisms of the primary and acute medical aid control; preparation and approval of the regulation of emergency service and organization of its activity in routine and in extraordinary situations; formation of standard methodical legal foundation for optimization of the functioning of institutions, departments and emergency specialists; development of recommended models of regional programs of emergency service development and reorganization in regions of Russian Federation.